STRATEGI KEPALA PESANTREN DALAM PENGEMBANGAN KOMPETENSI PROFESIONAL GURU UNTUK MENINGKATKAN MUTU PENDIDIKAN - Andika Faisal Lubis (UNISAN JURNAL, 2023)
The research purpose of this study is explain the strategic management the head of the islamic boarding school in developing the quality of teachers resources at the Ath Thoifah Al Manshuroh Islamic Boarding School Tegowangi Plemahan - Kediri. The research method is descriptive research in qualitative approach. The survey research obtained from interview, observation and documentation. The results study find that the strategic leadership the head of islamic boarding school in developing professional competencies of teachers to improve education quality at the Ath Thoifah Al Manshuroh Islamic Boarding School Tegowangi Plemahan – Kediri is divided into two strategic activities, the first is a formal strategy where the teachers are assigned by the institution to take part in study & training, both carried out by the school institution itself or by educational/training institutions, due to current or future job demands such as: courses, teacher training, seminars and MGMP programs. and non-formal strategy where the teachers will and effort on their own to train and develop themselves which related to their work or position such as: discipline, discussion and motivation.